Self-reported profile of chronic pain in students in the city of Nazaré da Mata - Pernambuco (Research, Society and Development, 2022)
Objective: To describe the profile of self-reported chronic pain in university students in the city of Nazaré da Mata, Pernambuco. Methodology: A cross-sectional epidemiological study was carried out with 40 students regularly enrolled in health courses who had chronic pain for a period of at least six months. Results: The results showed a young audience between 18-30 years old (75%), being the female sex prevalent (90%), and the most affected body sites were: head region (23.3%) and lumbar spine (19,2%). Most do not perform physical activity (55%), do not consume alcoholic beverages (65%), have not been diagnosed with pain (65%) and self-medicate (77.5%). Based on the research data, the finding of the profile of chronic pain in university students was obtained at Faculdade Santíssima Trindade in the city of Nazaré da Mata in the state of Pernambuco, being the majority in women, with the most affected body site being the head region followed by the lumbar region. Conclusion: This article contributes to the survey of the profile and prevalence of university students with chronic pain, directing attention to a particular public. However, further studies are needed to show the impact that chronic pain can have on the Brazilian population.